Post-mastectomy breast reconstruction in sub-Saharan Africa: a scoping review of availability, uptake, techniques, outcomes and barriers - Afolabi, Oluwatosin G.; Isshola, Damilola T.; Okunlola, Abiodun Idowu; Oluwajuyigbe, Mayowa E.; Adegbamigbe, Adedamola B. (International Surgery Journal, 2026)
Breast cancer survival in sub-Saharan Africa (SSA) is low, mastectomy predominates, and breast loss without reconstruction carries a documented quality-of-life cost. Post-mastectomy breast reconstruction may improve quality of life and the acceptability of surgery; however, its availability, uptake, and outcomes across SSA are poorly characterized. We aimed to map the existing evidence on this topic. Following the PRISMA extension for Scoping Reviews and the Arksey and O’Malley framework as refined by Levac and colleagues and the Joanna Briggs Institute, we searched PubMed/MEDLINE, Embase, Scopus, Web of Science, CINAHL and African Journals Online, with grey-literature and reference-list searching, for sources addressing post-mastectomy breast reconstruction in women treated for breast cancer in SSA. Sources were screened in Rayyan and charted across five domains: availability, uptake and techniques, patient perspectives, outcomes, and barriers and facilitators. The evidence was sparse, concentrated in a few countries, and dominated by qualitative studies and service surveys rather than by reconstruction outcome series. Reconstruction was often described as scarce and centralized, available at very few facilities, within mastectomy-dominated and largely out-of-pocket care pathways. Patient-level evidence concerned perceptions and acceptability, shaped by life stage, culture, and religion, rather than experience of reconstruction. No source reported oncological or standardized aesthetic outcomes after reconstruction; the only robust outcome evidence concerned the quality-of-life harm of mastectomy alone. Barriers include a scarcity of services, workforce shortages, costs, and cultural factors. Post-mastectomy breast reconstruction in SSA is a largely unmapped field characterized by minimal availability and an almost complete absence of outcome data in the literature. Registries, prospective outcome studies, and resource-stratified service planning are needed to support equitable, patient-centered breast cancer care.